Methodological Transformation in Islamic Theological Studies: From Classical Traditions to Contemporary Approaches - Ermawati, Erlin; Baimunah, Siti; Nursalim, Eko (Civiliza Publishing, 2025)
This study examines the characteristics of Islamic studies through theological approaches, analyzing the methodological transformation from classical to contemporary periods. The research employs qualitative methods with library research to investigate the evolution of Islamic theological discourse. Previous studies have shown significant developments in Islamic theology, particularly in the adaptation of classical traditions to modern challenges. This research aims to analyze the methodological characteristics of theological approaches in Islamic studies and examine contemporary theological responses to modernity and postmodernity challenges. The methodology utilizes qualitative content analysis of primary and secondary sources spanning classical to contemporary Islamic theological literature. Findings reveal a paradigmatic shift from apologetic-defensive orientation to integrative-interdisciplinary approaches, while maintaining epistemological continuity through Quranic and Prophetic authority. The study identifies three distinct periods: classical (emphasizing naql and aql methods), modern (hermeneutic-contextual approaches), and contemporary (integration of bayani, burhani, and irfani methods). Contemporary Islamic theology demonstrates anthropocentric characteristics that are more responsive to societal problems while preserving doctrinal authenticity. The discussion highlights the significance of methodological continuity and discontinuity, showing how contemporary theological approaches contribute to critical, moderate, and inclusive Islamic thought capable of addressing globalization, pluralism, and religious extremism. The study concludes that Islamic theological studies have evolved toward interdisciplinary approaches that ground Islamic values in modern contexts without compromising authenticity, positioning theology as an authentic moral voice addressing contemporary value disorientation and moral degradation.